2017
DOI: 10.1111/obr.12604
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and population differences in the genetic predisposition to human obesity

Abstract: SummaryObesity rates have escalated to the point of a global pandemic with varying prevalence across ethnic groups. These differences are partially explained by lifestyle factors in addition to genetic predisposition to obesity. This review provides a comprehensive examination of the ethnic differences in the genetic architecture of obesity. Using examples from evolution, heritability, admixture, monogenic and polygenic studies of obesity, we provide explanations for ethnic differences in the prevalence of obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 195 publications
(309 reference statements)
3
94
0
3
Order By: Relevance
“…As outlined in the section on genetic influences, Wardle proposed a role for behavioral susceptibility to OW/OB that is often expressed in terms of a genetic predisposition . Wardle and colleagues and others have suggested that genetic susceptibility to OW/OB could be mediated by appetitive traits such as a more avid appetite and lower satiety sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As outlined in the section on genetic influences, Wardle proposed a role for behavioral susceptibility to OW/OB that is often expressed in terms of a genetic predisposition . Wardle and colleagues and others have suggested that genetic susceptibility to OW/OB could be mediated by appetitive traits such as a more avid appetite and lower satiety sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…50,107,146,[230][231][232][233][234] As outlined in the section on genetic influences, Wardle 11,116,117 proposed a role for behavioral susceptibility to OW/OB that is often expressed in terms of a genetic predisposition. 16,22,113,235,236 Wardle and colleagues and others 16 have suggested that genetic susceptibility to OW/OB could be mediated by appetitive traits such as a more avid appetite and lower satiety sensitivity. This suggests that greater genetic susceptibility to OW/OB implies greater vulnerability to food-related environments (eg, an obesogenic food environment and feeding practices conducive to weight gain) that are linked to an imbalance of energy intake and expenditure and associated weight gain.…”
Section: Differential Susceptibility or Environmental Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, unhealthy diet and physical inactivity, in utero exposure, medical conditions (eg, depression), gut microbiota, sex, age, ethnicity, epigenetics, and genetics contribute to increased risk of obesity. Twin‐, family‐, and population‐based studies estimate that 40%‐75% of body mass index (BMI) variability is influenced by genetic factors . This has been confirmed by the identification of 940 polygenic loci that are associated with obesity .…”
Section: Introductionmentioning
confidence: 89%
“…Mouse models have been instrumental to elucidate the monogenic bases of obesity in humans . Altogether, these discoveries only account for a modest proportion of heritability of obesity, and more susceptibility genes have yet to be identified …”
Section: Introductionmentioning
confidence: 99%